Creating Acoustic Maps Employing Supercomputing Cluster - CZYŻEWSKI, Andrzej; KOTUS, Józef; SZCZODRAK, Maciej (Archives of Acoustics, 2011)
The implemented online urban noise pollution monitoring system is presented with regard to its conceptual assumptions and technical realization. A concept of the noise source parameters dynamic assessment is introduced. The idea of noise modeling, based on noise emission characteristics and emission simulations, was developed and practically utilized in the system. Furthermore, the working system architecture and the data acquisition scheme are described. The method for increasing the speed of noise map calculation employing a supercomputer is explained. The practical implementation of noise maps generation and visualization system is presented, together with introduced improvements in the domain of continuous noise monitoring and acoustic maps creation. Some results of tests performed using the system prototype are shown. The main focus is put on assessing the efficiency of the acoustic maps created with the discussed system, in comparison to results obtained with traditional methods.